Penyebab Unmet Need KB Dari Sudut Pandang Budaya Minangkabau di Nagari Lambah Kecamatan Ampek Angkek Kabupaten Agam - Fahrunnisa Fahrunnisa; Agus Meilinda (SEAJOM: The Southeast Asia Journal of Midwifery, 2015)
Unmet need for family planning (FP) is women that cannot meet their need of contraceptives. Factors to cause unmet need of contreaceptives seen from Minangkabau culture in Nagari Lambah of Ampek Angkek Sub-district of Agam District in 2014 was not yet known. This was a qualitative research. The informants were all couples of reproductive age (PUS) in Nagari Lambah with quote sampling. Data was collected with in-depth interviews to PUS and 4 public figures, namely Niniak Mamak, Alim Ulama, Cadiak Pandai, and Bundo Kanduang. The results showed that the causes of unmet need for FP were prohibition from husband, desire for certain gender of child, and negative myths and rumors about contraception. This culture was related to matriarch and Harato Pusako in Minangkabau. In addition to culture, religion also influenced respondents’ unmet need of FP.